A Review on The Relationship Between Tea Drinking and Breast Cancer - yu, Jingjing (Asian Journal Of Medical Technology, 2025)
The incidence of breast cancer remains high worldwide and is increasing each year in some regions. Despite the variety of current treatments for breast cancer, the preventive and therapeutic effects are still limited due to the highly heterogeneous nature and complex biological mechanisms of breast cancer. In recent years, tea consumption has emerged as a research focus because of its possible anti-cancer properties. Numerous preclinical studies have demonstrated that regular tea intake could potentially curb the progression of breast cancer by influencing various biological mechanisms, including signaling pathways, cell cycle regulation, and immune system responses, among others. Nonetheless, the findings from epidemiological studies show considerable variability, and the connection between tea drinking and both the risk and outlook for breast cancer is shaped by numerous elements. These include the specific type of tea consumed, the quantity consumed, individual genetic variations, and environmental influences.This article sums up the current research findings. It delves into the connection between tea consumption and the risk as well as prognosis of breast cancer among different regional populations. Meanwhile, it expounds on the potential molecular biological mechanisms behind it. The aim is to offer a theoretical foundation for the personalized prevention and treatment of breast cancer down the road.